EFEKTIVITAS FILTRAT BUAH MAHKOTA DEWA (Phaleria macro) SEBAGAI BIOINSEKTISIDA LARVA ULAT POLONG (Maruca testulalis) PADA TUMBUHAN KACANG PANJANG (Vigna unguiculata) - Devita Hardiyanti; Sigit Prafiadi; Revisika R (Jurnal Biosilampari : Jurnal Biologi, 2020)
This study aims to determine the effectiveness of the fruit filtrate of the Phaleria macro as bioinsecticide for the larvae of Maruca testulalis in long bean plants Vigna unguiculata. This research was conducted at the Integrated Science Laboratory of STKIP Muhammadiyah Manokwari in June 2019. The population used in this study was 150 larvae of Maruca testulalis. 7 treatment groups were consisting of 4 replications. The P0 treatment group was given 0.1 ml of reagent solution, then for treatment P1, P2, P3, P4, P5, and P6 each was given the filtrate from the Phaleria macro with a concentration of 20%, 30%, 40%, 50%, 60%, 70%. The results of data analysis using the Kruskal-Wallis test 5.708 <12.591 so that there was no effect of the bioinsecticide of the crown of gods on the larvae of Phaleria macro these results are influenced by the dose concentration that is not quite right. However, if it is seen from the results of the research data, it can be seen that there is an effect of giving the Phaleria macro fruit filtrate on the mortality of Maruca testulalis larvae. This effect is due to the presence of saponin compounds found in the Phaleria macro.